Interleukin-28B Polymorphisms Predict the Efficacy of Peginterferon Alpha in Patients With Chronic Hepatitis B: A Meta-Analysis - Ying, Sang-Yu; Hu, Yao-Ren; Gao, Guo-Sheng; Lou, Ke-Hong; Huang, Zhen (Frontiers in Medicine, 2021)
Background: Polyethylene glycol interferon alpha (PEG-IFN-α) is the most frequently used pharmacotherapeutic approach in patients infected with hepatitis B virus (HBV). Numerous studies have reported that interleukin-28B (IL-28B) genetic polymorphisms are related to the therapeutic efficacy of PEG-IFN-α, but the results are inconsistent. The present meta-analysis aimed to analyze the association between IL-28B genetic polymorphisms and the prognosis of patients with chronic hepatitis B (CHB) treated with PEG-IFN-α to inform clinical practice. Methods: PubMed, EBSCO, and Scopus databases were searched for relevant literature published before February 30, 2021. We calculated the crude odds ratios (ORs) with 95% confidence intervals (CIs) of the cited articles. A total of 2510 patients with CHB treated with PEG-IFN-α in 13 clinical cohort studies were analyzed. Results: The overall analysis demonstrated a potential association between IL-28B genetic polymorphisms and response to PEG-IFN-α; however, the association was not statistically significant. Furthermore, the subgroup analysis revealed that among patients with HBeAg-negative CHB, the rs12979860 CC genotype and rs8099917 TT genotype were associated with more significant treatment response to PEG-IFN-α (CC vs. non-CC: OR 2.78, 95% CI 1.00–7.76, I2 = 83%; TT vs. non-TT: OR 2.16, 95% CI 1.35–3.48, I2 = 0%). Among Asian patients with CHB, the rs12979860 CC genotype was associated with a more significant treatment response to PEG-IFN (CC vs. non-CC: OR 1.88, 95% CI 1.18–2.99, I2 = 0%). Conclusion: This meta-analysis revealed that the IL-28B rs12979860 CC genotype and rs8099917 TT genotype indicated a better treatment response than non-CC and non-TT genotypes for PEG-IFN-α in patients with CHB.